Porous copper-graphene heterostructures for cooling of electronic devices - Rho, Hokyun; Jang, Yea Sol; Kim, Sungmin; Bae, Sukang; Kim, Tae-Wook; Lee, Dong Su; Ha, Jun-Seok; Lee, Sang Hyun (ROYAL SOC CHEMISTRY, 2017)
Recently, research on micro-electronic and optoelectronic devices has been rapidly increasing. Parts and products related to these devices are becoming smaller and more integrated within circuits. As a result, the heat generated in devices has increased greatly. When excess heat is generated, important properties are affected such as efficiency and lifetime and, in severe cases, this can result in the failure of devices. Therefore, efficient cooling is required and it becomes necessary to study the heat dissipation properties of device materials. Research on heat-dissipating materials with high thermal conductivities and large surface areas, and which can transfer heat rapidly to facilitate progressive heat-release, is being actively pursued. In this study, a porous copper with reduced graphene oxide (pCu-rGO) heterostructure was fabricated by thermal annealing using Cu powder and GO. The thermal properties were then investigated and the results indicated that the pCu-rGO heterostructure exhibits a higher thermal conductivity than porous Cu. In addition, the thermal resistance of the sample was measured by applying it as a heat sink of a light emitting diode (LED). The result was 18.33% lower than that of bulk Cu. Also, when an overcurrent of 750 mA was applied for 144 hours, the luminance of bulk Cu decreased from 100% to 86.07%. On the other hand, the pCu-rGO showed that the luminance was maintained at 95.64%. Therefore, it is expected to resolve the existing problem of heat generation in electronic and optical devices.
Keywords: THERMAL MANAGEMENT; LAYER GRAPHENE; ENERGY-STORAGE; HEAT-TRANSFER; CONDUCTIVITY; DISSIPATION; TRANSISTORS